Increase in dietary protein content exacerbates colonic inflammation and tumorigenesis in azoxymethane-induced mouse colon carcinogenesis - Tak, Ka-Hee (Nutr Res Pract, 2017)
BACKGROUND/OBJECTIVE: The incidence of colorectal cancer (CRC) has been attributed to higher intake of fat and protein. However, reports on the relationship between protein intake and CRC are inconsistent, possibly due to the complexity of diet composition. In this study, we addressed a question whether alteration of protein intake is independently associated with colonic inflammation and colon carcinogenesis. MATERIALS/METHODS: Balb/c mice were randomly divided into 4 experimental groups: 20% protein (control, 20P, 20% casein/kg diet), 10% protein (10P, 10% casein/kg diet), 30% protein (30P, 30% casein/kg diet), and 50% protein (50P, 50% casein/kg diet) diet groups and were subjected to azoxymethane-dextran sodium sulfate induced colon carcinogenesis. RESULTS: As the protein content of the diet increased, clinical signs of colitis including loss of body weight, rectal bleeding, change in stool consistency, and shortening of the colon were worsened. This was associated with a significant decrease in the survival rate of the mice, an increase in proinflammatory protein expression in the colon, and an increase in mucosal cell proliferation. Further, colon tumor multiplicity was dramatically increased in the 30P (318%) and 50P (438%) groups compared with the control (20P) group. CONCLUSIONS: These results suggest that a high protein diet stimulates colon tumor formation by increasing colonic inflammation and proliferation.